Deep Foundation Design For Liquefaction Induced Lateral Spreads - Zia Zafir (Deep Foundations Institute, 2006)
Design of the deep foundations for the loads imposed by lateral spread include the estimate of the pressure applied by the liquefied material as well as amount of anticipated displacement. In the absence of a non-liquefiable cover over a liquefiable layer, it is possible to design the foundation system just for the additional pressure applied by the flow slides. On the other hand, if a non-liquefiable layer exists above the liquefied zone, the foundation should be designed for anticipated movements. To completely account for liquefaction and/or lateral spread and their interaction with the deep foundation system, a coupled soil-structure interaction (SSI) analysis should be performed. However, a complete SSI analysis may not be feasible for most of the projects. This paper will present recent advances in analysis techniques and simplified methods to design deep foundations for liquefaction and lateral spreading. In addition, a case history of the Rancho California Bridge in southern California located within 1 km of the active Elsinore fault will be presented. One of the bridge abutments is underlain by potentially liquefiable layers. The pressure applied by the liquefiable layer was estimated to be greater than the shear capacity of the 36-inch CIDH piles designed for the abutment. However, with limited ground improvement and more careful analyses incorporating structural effects of CIDH piles, resulting design and construction resulted in a factor of safety greater than 1 against slope failure. The recommended approach was generally consistent with the recently published, and AASHTO sponsored, NCHRP 12-49 project regarding seismic design guidelines for new bridges and the effects of seismic displacements against bridge foundations.